LARVASIDA EKSTRAK BIJI PEPAYA (Carica papaya L) TERHADAP KEMATIAN LARVA INSTAR III AEDES AEGYPTI - Liya Ni'matul Maula; Musfirah Musfirah (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2022)
Dengue Hemorrhagic Fever (DHF) is acute fever caused dengue virus transmitted by bite of Aedes aegypti mosquito. Chemically insecticides as vector control can be negative impact to environmental and health body. Alternative biological control is papaya seeds which contain karpain alkaloids, flavonoids and papain. This study determined the effectiveness with variations in concentration and time using papaya seed extract on the mortality of Aedes sp. larvae. The study used true experiment and using post-test only with control group design. Data processing used computer program Statistical Package for the Social Sciences with Anova analysis and Probit analysis. The concentration used was 0,1%-1%. Observations were observed at 1st to 6th, 9th, 12th, 15th, 18th, 21st and 24th hours. The highest mortality rate at 1% concentration and positive control with 100% percentage. Based on Mann-whitney test that positive control (temefos 0,01%)  had a significant difference in mortality of larvae with concentrations of papaya seed extract 0,1%, 0,2%, 0,3%, 0,4% and 0,5% (p value < 0,05), it means papaya seed extract can be used larvacide. Papaya seed extract had a significant difference  mortality of Aedes aegypti larvae with negative control (well water) at each concentration, it means papaya seed extract can be used as larvacide too. LC50 and LT50 values were obtained based on probit test values of 2,491% and 8,751 hours. It is necessary to control and prevent dengue fever by using natural larvicides.